Differential Expression Profile of lncRNA in Glioma Cells and the Effect of lncRNA NKX3-1 on Glioma Cells Through Fem1b/SPDEF Pathway - Cai, Yang; Wang, Ming; Cui, Yan; Tan, Zhigang; Jiang, Yugang (Frontiers in Oncology, 2021)
Objective: To explore the differential expression profile of lncRNA in glioma cells and the effect of lncRNA NKX3-1 on glioma cells. Methods: Firstly, Glioma related data were downloaded from TCGA database and analysed by bioinformatics method, then lncRNA NKX3-1 was selected for subsequent experiments. qRT-PCR was used to detect the expression of lncRNA NKX3-1 in glioma tumor specimens,. Fluorescence in situ hybridization (FISH) was used to determine the subcellular localization of lncRNA NKX3-1. Cell proliferation, cell apoptosis, cell invasion were detected by CCK-8, flow cytometry, cell scratch and transwell assay. And the downstream pathway of lncRNA NKX3-1 was explored by luciferase assay, and detected by western blot, transwell and cell scratch assay. Results: We obtained the differential expression profile of lncRNA in glioma. LncRNA NKX3-1 was significantly increased in glioma tumor tissues. LncRNA NKX3-1 was localized in nucleus. The proliferation, invasion and migration of glioma cells were significantly increased in the lncRNA NKX3-1 overexpression group (P<0.05), the ability of apoptosis was significantly decreased (P<0.05). In nude mice, tumor volume and tumor weight were significantly increased in lncRNA NKX3-1 overexpression group (P<0.05). LncRNA NKX3-1 significantly increased the luciferase activity of Fem1b 3 '-UTR-WT reporter genes (P<0.05) and increased SPDEF protein levels (P<0.05). FEM1B protein level was significantly decreased. Cell invasion and migration were significantly enhanced in lncRNA NKX3-1 overexpression group +SPDEF group (P<0.05). Conclusion: We obtained the differential expression profile of lncRNAs in glioma, and found that lncRNA NKX3-1 play an important role in promoting cancer through the Fem1b/SPDEF pathway.